Track and field for young champions - Antonacci, Robert Joseph, 1916-; Schoor, Gene; Mullins, Frank (New York McGraw-Hill, 1974)
Examines the history, equipment, rules, and techniques of each event in track and field.
Keywords: Track -- athletics -- Juvenile literature